Effectiveness of differentiated learning in improving 4th-grade reading skills MIS Masino - Hilmy Hafidah; Aliem Bahri (Universitas Pendidikan Indonesia, 2025)
The main issue addressed in this study is the low reading comprehension skills of students, which are attributed to the use of monotonous teaching approaches and methods, as well as learning media that are unengaging and irrelevant to the current context. This study aims to determine the effectiveness of differentiated instruction in improving the reading comprehension skills of fourth-grade students. The research employed an experimental method using a one-group pretest-posttest Design. The subjects of this study were all fourth-grade students at MIS Masino, totaling seventeen individuals. The data collection techniques included pretest and posttest assessments, observation, and documentation. The results showed a significant improvement in students’ reading comprehension skills after the implementation of differentiated instruction. Students' average scores during the pretest were categorized as fair and increased to a good category in the posttest. The statistical analysis using the t-test indicates that differentiated instruction had a positive effect on enhancing students' reading comprehension skills. It can be concluded that differentiated instruction is effective in improving students' reading comprehension skills and can serve as a relevant strategy for teaching the Indonesian language at the elementary school level. Abstrak Permasalahan utama dalam penelitian ini adalah rendahnya keterampilan membaca pemahaman peserta didik, yang disebabkan oleh penggunaan pendekatan dan metode pengajaran yang monoton serta media pembelajaran yang kurang menarik dan tidak relevan. Penelitian ini bertujuan untuk mengetahui efektivitas pembelajaran berdiferensiasi dalam meningkatkan keterampilan membaca pemahaman peserta didik. Penelitian ini menggunakan metode eksperimen dengan desain One Group Pretest-Posttest. Subjek penelitian ini adalah seluruh peserta didik kelas IV MIS Masino yang berjumlah tujuh belas orang. Teknik pengumpulan data yang digunakan mencakup pemberian pretest dan posttest, observasi, serta dokumentasi. Hasil penelitian menunjukkan adanya peningkatan yang signifikan dalam keterampilan membaca pemahaman peserta didik setelah diterapkannya pembelajaran berdiferensiasi. Skor rata-rata peserta didik pada saat pretest berada pada kategori cukup dan mengalami peningkatan hingga masuk ke dalam kategori baik setelah posttest. Uji statistik menggunakan uji-t mengindikasikan bahwa pembelajaran berdiferensiasi memberikan pengaruh positif terhadap peningkatan keterampilan membaca pemahaman peserta didik. Dapat disimpulkan bahwa pembelajaran berdiferensiasi efektif meningkatkan keterampilan membaca pemahaman peserta didik dan dapat menjadi strategi yang relevan dalam pembelajaran Bahasa Indonesia di sekolah dasar. Kata Kunci: keterampilan membaca; pemahaman membaca; pembelajaran berdiferensiasi